PENGARUH PEMANGKASAN TAJUK TANAMAN KOPI DAN PEMUPUKAN TERHADAP PENCUCIAN UNSUR HARA PADA SISTEM AGROFORESTRI KOPI - Nurcholis, Omar; Wicaksono, Kurniawan Sigit; Fata, Yulia Amirul; Kurniawan, Syahrul (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2026)
Tree management such as pruning of coffee canopy and fertilization in coffee-based agroforestry systems plays a crucial role in reducing nutrient losses through leaching. This study aims to evaluate the impact of coffee pruning and fertilization management on nutrient leaching. The study was conducted in a coffee agroforestry system in the Universitas Brawijaya forest from February to August 2023. This study used a split-split plot design with main plots of coffee canopy pruning (T1: pruned coffee, T2: unpruned coffee), subplots of fertilizer type (O: organic fertilizer, A: inorganic fertilizer, M: 50% organic + 50% inorganic), and sub-plots of fertilizer dosage (D1: dosage based on farmer practice, D2: recommended dosage based on the Coffee and Cocoa Research Center, D3: dosage based on the replacement of nutrients removed by the coffee bean harvest). The study had 18 treatments with 4 replicates, resulting in 72 experimental plots. The variables measured included ammonium, nitrate, phosphorus, and potassium concentrations. Sampling of nutrient leaching was conducted four times over a period of six months (February-July), specifically in February, March, April, and July 2023 at 0.5 m distance from the coffee stem in 0.6 m depth of soil. The results showed that pruning coffee plants had a significant effect (P < 0.05) on nutrient losses due to leaching, especially nitrate and potassium. A pruned coffee canopy in an agroforestry system was able to reduce nitrate and potassium leaching by 30% and 13%, respectively, compared to unpruned coffee in the agroforestry land. Nutrient loss of phosphorus through leaching was found to be 21% greater in treatment D1 compared to D2. However, this study did not find a significant effect of the interaction between pruning and fertilization in reducing the leaching of nitrogen, phosphorus, and potassium nutrients.